Violent conflicts and state capacity: Evidence from Sub-Saharan Africa - Adedoyin Babajide (Elsevier, 2021)
This paper investigates the impacts of conflicts on state-capacity in Sub-Saharan Africa (SSA), a region that has recorded a disproportionate number of armed conflicts and has a high presence in the Fragile States Index rankings. Individually, both conflicts and state-capacity are known to have important implications for economic development, which underscore their relevance for developing countries. Our aim here is to analyze the relationship between them and for this, we analyze a panel of 49 SSA countries spanning 2000–2015. Our results suggest that the effect of conflicts on state-capacity depends on the variable used to proxy state-capacity is important: conflicts diminish state-capacity when tax revenue is used as the proxy, but the effect is positive when proxied by military expenditure. Other proxies consider include regulatory quality, rule of law, and government effectiveness.